2003
DOI: 10.1128/iai.71.4.1872-1879.2003
|View full text |Cite
|
Sign up to set email alerts
|

Novel Virulence-Associated Type II Secretion System Unique to High-PathogenicityYersinia enterocolitica

Abstract: Yersinia enterocolitica strains comprise an important group of bacterial enteropathogens that cause a broad range of gastrointestinal syndromes. Three groups are distinguishable within this bacterial species, namely, the nonpathogenic group (biotype 1A strains), the low-pathogenicity, non-mouse-lethal group (biotypes 2 to 5), and the high-pathogenicity, mouse-lethal group (biotype 1B). To date, the presence of the high-pathogenicity island (HPI), a chromosomal locus that encodes the yersiniabactin system (invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 54 publications
6
61
0
1
Order By: Relevance
“…This finding is in accordance with many previous studies [1,4]. Also Delor and Cornelis considered that the Yersinia enterotoxin was the cause of diarrhoea in young rabbits and consequently was the major factor involved in the Y. enterocolitica-associated diarrhoea in young children.…”
Section: Antimicrobial Sensitivity Testssupporting
confidence: 82%
See 2 more Smart Citations
“…This finding is in accordance with many previous studies [1,4]. Also Delor and Cornelis considered that the Yersinia enterotoxin was the cause of diarrhoea in young rabbits and consequently was the major factor involved in the Y. enterocolitica-associated diarrhoea in young children.…”
Section: Antimicrobial Sensitivity Testssupporting
confidence: 82%
“…This result is in keeping with Grant et al [9] and Iwobi et al [4] who found that the Peyer's patches ٢٠٠9 ،٢ ‫العدد‬ ‫عرش،‬ ‫اخلامس‬ ‫املجلد‬ ‫العاملية،‬ ‫الصحة‬ ‫منظمة‬ ‫املتوسط،‬ ‫لرشق‬ ‫الصحية‬ ‫املجلة‬ of the intestine were the primary sites for infection with Yersinia. Moreover, enterotoxin production was positive in infant mice with ratios of intestine:total body weight of 0.08 and 0.083.…”
Section: Antimicrobial Sensitivity Testssupporting
confidence: 81%
See 1 more Smart Citation
“…The native isolates of Y. enterocolitica did exhibit the prevalence of yst and ail genes, which are unique to pathogenic isolates of this species. The native isolates obtained in our study showed the presence of the yts1 gene, which is invariably present only in highly pathogenic group of Y. enterocolitica [25]. Besides, both the native isolates of Y. enterocolitica were also positive for two other important virulence factors such as rovA and myfF (Fig.…”
Section: Discussionsupporting
confidence: 49%
“…The two secretion systems have been shown to be required for full virulence in oral infection models (17,18,23). Studies using a mouse model have indicated about a 10-fold increase in the 50% lethal dose of ysa mutants compared to that of wild-type strains, and ysa mutants are defective for colonization of the intestinal tract (17,23).…”
mentioning
confidence: 99%